Leveraging Artificial Intelligence to Enhance Inclusive Teaching for Students with Intellectual Disabilities in Nigerian Universities - Bessong, Bessong Emmanuel; Atah, Cletus Akpo; Olom, Patricia Akwaya; Nkurika Akeke, Mercy Akeke; Erim, Costly Manyo; Udie, Elizabeth Akwenaboye; Emogor, Elogbo, Eno; Udida, Fabian Ugbe; Azu, Sunday Begianpuye; Odije, Patrick Elizabeth; Olofu, Paul Agbade; Amakaino Utoware, Jude Daniel; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Artificial Intelligence (AI) offers significant opportunities for advancing inclusive teaching, particularly for students with intellectual disabilities in Nigerian universities. By leveraging AI tools, educators can help close learning gaps, boost student engagement, and promote equitable learning experiences. This study explores the extent to which lecturers use AI tools to support inclusive teaching and examines how these tools influence the academic engagement of students with intellectual disabilities. Methods: A descriptive survey design was employed, involving 600 lecturers drawn through accidental sampling from universities across Nigeria. Data were collected using a structured questionnaire that assessed the use of AI tools, lecturers’ perceptions of their effectiveness, and their impact on students’ academic engagement. Descriptive statistics (mean and standard deviation) were used to summarize the responses. At the same time, independent t-tests and multiple regression analyses were employed to test the hypotheses at the 0.05 level of significance. Results: Findings indicated that lecturers’ overall use of AI tools in inclusive teaching was low. Nevertheless, in cases where AI was applied, it was perceived to have a strong positive effect on students’ engagement. Specifically, lecturers noted improvements in students’ attention, participation, interest in learning tasks, and task completion when AI tools were integrated into instruction. Further analysis revealed that factors such as gender, teaching experience, and the type of university did not significantly affect how AI was adopted. Instead, what mattered most was how actively lecturers integrated AI tools into their teaching. This level of engagement proved to be the strongest factor linked to improved student participation and learning outcomes. Conclusions: The study highlights AI’s transformative potential in fostering inclusive education in Nigerian universities. Although current utilization remains limited, the reported benefits suggest that greater investment in lecturer training, technological infrastructure, and supportive policies could expand the role of AI in inclusive teaching. These insights contribute to global efforts toward Sustainable Development Goal 4, which emphasizes inclusive and equitable quality education for all.